Anthropogenic and environmental factors affect the tree line position of Fagus sylvatica along the Apennines (Italy). (4th September 2018) - Bonanomi, Giuliano; Rita, Angelo; Allevato, Emilia; Cesarano, Gaspare; Saulino, Luigi; Di Pasquale, Gaetano; Allegrezza, Marina; Pesaresi, Simone; Borghetti, Marco; Rossi, Sergio; Saracino, Antonio
Abstract: Aim: High‐elevation forest line or tree line is an ecological ecotone representing the upper elevation thermal limit for forest development. The current tree line position is the result of the past human activity interacting with climatic and topographic conditions. In this study, we investigate how climate, local topographic factors and anthropogenic disturbance currently affect tree line distribution. Location: Apennine Mountains, 900 km latitudinal gradient along the Italian Peninsula. Methods: Overall, 302 mountain peaks were studied, comprising 3, 622 km of measured tree lines. The position of the Fagus sylvatica tree line in all peaks was assessed and correlated with 58 selected variables representing climate, topography and human disturbance. Results: The mean tree line elevation was 1, 589 m a.s.l., with considerable variability among peaks. Contrary to our expectations, the tree line elevation was lower in the warmer southerly exposed slopes compared to north‐facing aspects, where we found the highest tree line (2, 141 m a.s.l.). Correlation analysis indicates that both climatic and human density variables are associated with tree line elevation, with the climate having more influence in high elevation mountains, while human impact plays a prominent role in low elevation mountain peaks. Specifically, we found negative correlations between density of the resident population around each peak and tree line elevation at all examined dates (1861, 1921, and 2011), suggesting a pervasive negative impact of human activity on tree lines. As regards climatic variables, tree line elevation showed a stronger negative correlation with winter and spring months temperature than with mean annual temperature. Noteworthy, climatic variables had stronger effect on high elevation peaks (>1, 900 m a.s.l.) compared with low elevation ones (<1, 900 m a.s.l.). Main Conclusion: Our data provide evidence that the current position of the F. sylvatica tree line in the Apennines is heavily depressed as a result of a complex interaction between climatic factors and the past human pressure.